Understanding Entrepreneurial Intentions of Albanian Business Students Based on the Theory of Planned Behaviour - Blendi Shima; Babu George (International School for Social and Business Studies, 2020)
This research aims to contribute to the understanding of the effect of entrepreneurship education on entrepreneurial intentions among university business students in Albania. A model interlinking entrepreneurship education and entrepreneurial intention is proposed based on the theory of planned behaviour. Factors related to education that affect the entrepreneurial intentions among business students in Albania are identified and measured. Analysis of the data revealed significant relationships between personal attitudes and entrepreneurial intentions. Subjective norms and perceived control over the entrepreneurial abilities were both not significantly related to entrepreneurial intentions. Discussion of results is presented and future research possibilities are suggested.